A Legal Analysis of Disparities in Judicial Decisions Regarding Human Trafficking Crimes - Saputri, Widya Riska; Toteles, Aris; Theresia, Louise (Dinasti Research, 2025)
Disparities in judges' decisions in human trafficking cases indicate inconsistency in delivering verdicts for similar or related cases. The primary objective of this study is to identify various factors influencing the differences in judges' decisions in human trafficking cases, including how judges assess the elements of the case, consider aggravating and mitigating circumstances, and apply the law appropriately to realize justice in court rulings. The research method used is normative juridical, with data collection techniques including the study of court decisions from the Palangka Raya District Court, books, and scientific journals. The research findings show that there are several disparities in judges' rulings on similar cases. In the judicial process, a judge's conviction is based on legally valid and admissible evidence. Sentences, such as imprisonment and fines, are influenced by various factors, including mitigating conditionslike young age, confession, remorse, and the defendant's attitude during the trial. Disparities in rulings occur due to differences in judges' convictions and the lack of clear guidelines insentencing.